P125: Willingness of ED staff to implement a brief intimate partner violence case-finding tool. (15th May 2017) - Vonkeman, J.; Atkinson, P.R.; Fraser, J.; McCloskey, R.
Abstract : Introduction: Domestic violence (DV) rates in smaller cities have been reported to be some of the highest in Canada. It is highly likely that emergency department staff will come across victims of intimate partner violence (IPV) in their daily practice. However, elsewhere we have found a lack of knowledge of current tools as well as lack of training in ED staff. Furthermore, these findings may also be reflected by low rates of IPV documentation, especially in high-risk cases. The purpose of the current study is to determine if ED staff would be willing to implement a brief IPV screening tool, the Partner Violence Screen (PVS) in their daily practice. It consists of the 3 questions: Have you ever been hit, kicked, punched or otherwise hurt by someone within the past year, and if so, by whom? Do you feel safe in your current relationship? Is there a partner from a previous relationship that is making you feel unsafe now?Methods: A cross-sectional online survey was distributed to ED staff (LPNs, NPs, Physicians, Residents, RNs) via staff email lists three times between July and October 2016, with a response rate of 45.9% (n=55). The survey included a 5-question Likert scale. The primary outcome was whether ED staff are willing to implement a new case-finding tool in their daily practice. The secondary outcome was to assess whether staff would find this tool beneficial in case-finding for IPV.Results: 43.6% of staff responded that they are likely to use the tool routinely, 29.1% were unsure, and 2.7% very likely. 7.27% and 3.64% stated their predicted use as unlikely and very unlikely, respectively. In addition, 43.6% of staff thought that the PVS would be beneficial in case finding for IPV, 40% were unsure, 12.7% thought very likely, 1.82% unlikely, and 1.82% very unlikely.Conclusion: These findings suggest that emergency department staff may be receptive to and find the introduction of the PVS beneficial in identifying cases of IPV. Future directions will include the introduction of this tool through a knowledge translation education piece in order improve the identification process for and awareness of a high-risk condition in a vulnerable population group.